2019
DOI: 10.1590/0366-69132019653752626
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogy and preliminary assessment of the potential uses of alluvial clays from Batouri (Eastern-Cameroon)

Abstract: This study aimed at assessing the potential uses of alluvial clayey materials from Batouri. Their mineralogical, chemical and some physicomechanical characteristics are presented with some characteristics of fired bricks at 900, 950, 1000, 1050 and 1100 °C. The raw materials consisted of kaolinite, quartz, K-feldspars, anatase, and goethite. The phases formed during the firing process were mullite, quartz, hematite, and anatase. The linear shrinkage increased with firing temperature and remained <12% while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
7
2
Order By: Relevance
“…σ f shows its minimum values at 1100 °C for all the studied materials (respectively 2.65, 2.51, 2.41, and 2.86 MPa for NJI-T1, NJI-T2, NB-T1 and NB-T2). Overall, for the same material, this parameter decreases when firing temperature increases, contrary to many previous studies [ 19 , 22 , 34 ]. This decrease reveals weak densification due to poor mullitization [ 22 , 34 ].…”
Section: Resultscontrasting
confidence: 92%
See 1 more Smart Citation
“…σ f shows its minimum values at 1100 °C for all the studied materials (respectively 2.65, 2.51, 2.41, and 2.86 MPa for NJI-T1, NJI-T2, NB-T1 and NB-T2). Overall, for the same material, this parameter decreases when firing temperature increases, contrary to many previous studies [ 19 , 22 , 34 ]. This decrease reveals weak densification due to poor mullitization [ 22 , 34 ].…”
Section: Resultscontrasting
confidence: 92%
“…The quartz peaks comparatively high intensity in these materials XRD patterns suggested that this mineral might exist in large amounts [ 17 ]. This was supported by the high SiO 2 /Al 2 O 3 ratios ( Table 1 ), which show that each raw material has weak kaolinite proportions as indicated by the peak of this mineral [ 34 ]. Hematite is also found in low quantities considering its peak and may induce a light red coloration of raw material and fired bricks.…”
Section: Resultsmentioning
confidence: 87%
“…The contents of the uxing oxides in the ISQW samples can favor su cient sintering during ring as vitreous phase formations is guaranteed. Sintering temperature often is an important processing variable which can in uence signi cantly the nal ceramic product (Serra et al 2014; Diko-Makia and Ligege 2020) and poor vitreous phase formation usually in uenced negatively the cohesion of the red products (Onana et al 2019). Based on chemical speci cations, the concentrations of SiO 2 , Al 2 O 3 , MgO and Fe 2 O 3 are within the allowable international parameters for ceramics formulations as the ISQW materials showed richness in SiO 2 and Al 2 O 3 which have great in uence in development of ceramic materials.…”
Section: Mineralogy and Chemical Characteristics Of The Indurated Shalementioning
confidence: 99%
“…At the ring temperature of 1000 o C, an increased in the bulk density and ring linear shrinkage were observed which partially agrees with decreased WA. For roo ng tiles application, after ring to the temperature of about 1000 o C, raw materials with FS ≥ 5.7 MPa (Souza et al 2002;Onana et al 2019) and WA < 20% (Onana et al 2019) are considered valuable for roo ng tile manufacturing (Table 5). Therefore the red temperature of 1000 o C served as suitable condition for the beginning of liquid phase sintering, increased material densi cation and mechanical strength development of the raw materials for the production of roo ng tiles.…”
Section: Ceramics Properties Of the Quarry Wastementioning
confidence: 99%
“…In the present research, the temperatures range between 900 and 1100 °C. FS increase can be chemically related to mullite formation from 900 °C [29,30]. Except for NL mixtures at 900 °C, the studied materials exhibit flexural strength values > 2 MPa and can be used for structural bricks manufacturing [24].…”
Section: Physical and Mechanical Characterizationmentioning
confidence: 99%